Estudo in vitro de um protocolo de retratamento endodôntico realizado com o Sistema Protaper Next em molares inferiores - (:unkn) unknown (Universidade Federal do Amazonas, 2017)
The purpose of this study was to evaluate a protocol for endodontic retreatment, using Protaper Next instruments, to evaluate the occurrence of apical transportation using CT. To perform the experiment, 40 mandibular molars were selected, with mesial root canal curvature between 30° and canal curvature radius less than or equal to 10 mm. Size 10 K-type instruments were used to determine the presence of independent foramen. In order to standardize the samples, the crowns were partially sectioned in 16 mm and all the specimens were inserted in resin blocks, to standardize the tomographies in the same position before, during and after instrumentation and retreatment. They were also submitted to the same instrumentation and obturation process, and were then randomly separated (n = 10) into four experimental groups: PTU group, in which the instrument used to remove gutta-percha was Protaper F2 (25.08); Group R25 and Group X2 where the Reciproc - R25 (25.08) and Protaper Next - X2 (25.06) instruments were used for the same purpose, respectively; And Group X3, where the X2 instruments were used sequentially for the removal of gutta-percha and X3 (30.07) for channel remodeling, both belonging to the Protaper Next system. Apical deviation was assessed by applying formulas to values obtained before and after instrumentation, and with the data obtained it was also possible to analyze centering ratio and percentual area increase. Data were subjected to the Kruskal-Wallis Test and the Dunn Multiple Comparisons Test. The results of the apical deviation presented no significant difference between the experimental groups (p <0.05). The methodology and the results lead to the conclusion that the experimental groups did not produce a statistically significant difference in apical deviation.
Keywords: Endodontia; Retratamento; Transporte Apical; Protaper Next; CIÊNCIAS DA SAÚDE: ODONTOLOGIA